The Phenomenon of Harassment Among University Students (Applied study on the University of Mutah) - Al-Bahri, Nasreen A. (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aimed to investigate the phenomenon of sexual harassment, its causes, and the locations where female students at Mu’tah University experience it. Additionally, it aimed to determine the variations in the occurrence of harassment among female students of Mu’tah University based on factors such as year of study, age, college residency and monthly income Methods: The study employed a descriptive analytical approach, and the study population consisted of 432 students. A sexual harassment questionnaire was developed, comprising a total of 35 paragraphs. Results: The study’s findings revealed patterns in the occurrence of harassment, significant differences related to various factors, and insights into the phenomenon of harassment among Mu’tah University students. These factors included the year of study, place of residence, and monthly income. Conclusions: This research lays the foundation for future studies on harassment. It also suggests that the university should establish dedicated centers in collaboration with other institutions to explore these phenomena. Such efforts would contribute to fostering a supportive environment characterized by order and stability.